2005
DOI: 10.1021/jf0502808
|View full text |Cite
|
Sign up to set email alerts
|

High-Pressure Induced Physicochemical and Functional Modifications of Low-Density Lipoproteins from Hen Egg Yolk

Abstract: High-pressure treatment represents a potential method to stabilize microbiologically agricultural raw materials that are sensitive to heat treatments. Low-density lipoproteins (LDL), the main contributors to the exceptional emulsifying properties of yolk, are particularly sensitive to heat treatment. In this study, high-pressure treatments have been performed on LDL, and their impact on LDL physicochemical and emulsifying properties has been assessed. LDL dispersions at two pH levels (pH 3 and 8) were treated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 21 publications
0
22
0
Order By: Relevance
“…43,46,47 The broad peak at ∼80°C is expected to correspond to the most abundant proteins in yolk, LDL, which is confirmed by studies on pure human LDL. 48 However, in pure egg LDL at pH 8 the peak is reported at ∼70°C, 49 thus DSC experiments do not clarify the matter. Stability studies have reported that LDL is stable below 60°C, but it is fully aggregated after heating it at 70°C for 5 min, 44 while higher temperatures are reported for shorter heat treatments (72-76°C for 2.5 min.…”
Section: Molecular Considerations For the Cooking Of 6x°c Eggsmentioning
confidence: 99%
“…43,46,47 The broad peak at ∼80°C is expected to correspond to the most abundant proteins in yolk, LDL, which is confirmed by studies on pure human LDL. 48 However, in pure egg LDL at pH 8 the peak is reported at ∼70°C, 49 thus DSC experiments do not clarify the matter. Stability studies have reported that LDL is stable below 60°C, but it is fully aggregated after heating it at 70°C for 5 min, 44 while higher temperatures are reported for shorter heat treatments (72-76°C for 2.5 min.…”
Section: Molecular Considerations For the Cooking Of 6x°c Eggsmentioning
confidence: 99%
“…3. treatment provokes a denaturation of LDL, leading to a disruption of the LDL structure and a reorganization by aggregation of LDL components (Speroni et al, 2005). The results indicate that LDL most likely undergoes a 'cluster-fusion' aggregation mechanism upon sufficient heating.…”
Section: Effect Of Heat and Enzymatic Treatment On Egg Yolk Plasmamentioning
confidence: 88%
“…Anton and coworkers purified LDL from egg yolk by gel filtration and found LDL to contain five major apoproteins While the effect of pH, ionic strength, processing and enzyme treatment on emulsion properties of egg yolk has been studied (Daimer & Kulozik, 2008;Guilmineau & Kulozik, 2006a, 2006bLe Denmat et al, 2000;Mine, 1998a), not much focus has been put on the effect of these parameters on LDL structure. One of the important functional properties of egg yolk plasma is its ability to undergo aggregation upon heat treatment, which plays an important role in the textural properties of final food products (Speroni et al, 2005). Heat stability is often desirable in emulsions, for instance to have the possibility to pasteurize them to assure microbiological safety etc.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Egg yolk is widely used in the food industry due to the excellent functional properties of its lipoproteins, such as flavor, aroma, color, viscosity, emulsifying, and foaming (Fennema, 1993). Denaturation of egg yolk proteins resulted in functional modifications, such as emulsifying and rheological properties (Ahmed et al, 2003;Speroni et al, 2005).…”
Section: Introductionmentioning
confidence: 99%